2021
DOI: 10.1002/aoc.6138
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation induced emission (AIE)‐active N‐arylated ferrocenyl pyrazole‐based push–pull chromophores: Structural, photophysical, theoretical and effect of substitution on second‐order non‐linear optical properties

Abstract: In this study, we report the synthesis and structural characterization of Narylated ferrocenyl pyrazole [Fc-Pz-(CF 3)-C 6 H 5-R] (R = CH 3 , 1; OCH 3 2), where Pz = pyrazole and Fc = ferrocenyl = Fe(η 5-C 5 H 5)(η 5-C 5 H 4) chromophores with D-π-A-π-D system. The solvatochromic behaviour of compounds 1 and 2 was investigated in various solvents from non-polar to polar. When solvent polarity increases, the charge transfer process produces the more polarized excited state, and consequently, positive solvatochro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…These elevated dihedral angles could potentially amplify the efficiency of second harmonic generation (SHG) within the chromophores. Also, chromophore 2 shows multiple non‐covalent interactions like H‐bonding and C−H…π within the arrangement of its crystalline structure, which induce NLO signals in bulk by preventing the antiparallel arrangement [21,23] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These elevated dihedral angles could potentially amplify the efficiency of second harmonic generation (SHG) within the chromophores. Also, chromophore 2 shows multiple non‐covalent interactions like H‐bonding and C−H…π within the arrangement of its crystalline structure, which induce NLO signals in bulk by preventing the antiparallel arrangement [21,23] …”
Section: Resultsmentioning
confidence: 99%
“…Fine‐tuning and switching of the electronic properties of ferrocene are considerably significant, so more appended molecules have been researched on ferrocene donors with variable acceptors such as porphyrinoids, [14] metal carbonyls [15] and heteroaromatic [16] to achieve remarkable NLO properties. Also, our research group has reported ferrocene substituted chromophores with various shapes such as linear, [17] Y‐shaped quinoxalines, [18] imidazole, [19] BF 2 complexes, [20] schiff base complexes, [21] N‐arylated pyrazole, [22] multi‐donor, [23a] and naphthalic anhydride [24a] derivatives which showed better SHG efficiencies. Among these compounds, the broken symmetry approach [25] improved the NLO efficiencies of centrosymmetric borasiloxanes [26] .…”
Section: Introductionmentioning
confidence: 99%
“…[23,30] The moderate fluorescence of 1 and 2 may be ascribed to the photo-induced electron transfer (PET) effect. [17][18][19][20][21][22][23] The poor quantum yield of 1 relative to that of 2 may be attributed to the presence of more flexible groups promoting vibrational relaxation in 1 (Figures 2b and S5). Apart from comparative fluorescence behaviour, the structures of emission bands of 1 and 2 were also quite different and may be associated with the excited state dimeric association in 1, whereas there was an extensive HÁÁÁbonding chain in 2, considering their chemical structures.…”
Section: Spectral Studies and Selective Fe 3+ Detectionmentioning
confidence: 99%
“…[14][15][16][17][18] In addition, the incorporation of redox active ferrocene units in conjugation with the -CH=Nbond of the Schiff base provide an exceptional aid for recognition of analytes due to its strong donor-πacceptor properties. [19] Among metallocenes, ferrocene derivatives have shown excellent biostability and biological activity, nontoxicity, favourable electronic properties, and these have been extensively explored for the detection of neutral molecules, cations, anions, and ion-pairs. [20][21][22][23] Although the design of the probes for detection of metal ions such as Hg 2+ , Pb 2+ , Cd 2+ and Zn 2+ has been well documented in the literature, [24][25][26][27][28] however reports on recognition of redox active ions such as Fe 2+ /Fe 3+ and Cu + /Cu 2+ are relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…presented the modification of 2‐aminophenol by using ferrocene group, and the fabricated ferrocenyl Schiff‐bases [Fc−C(H) = N−C 6 H 3 (OH)(R)] (R = H (compound 5 ), NO 2 (compound 6 )) launched dense fluorescence upon aggregation. [ 139 ] The PL spectra and the time‐resolved luminescence spectra of ferrocenyl Schiff‐bases in acetonitrile–water system disclosed that the enhanced emission intensity and longer fluorescence lifetime at a water content of 90%. Kurtz‐Perry powder method was utilized to confirm the SHG efficiency of the crystals of compound 5 and 6 .…”
Section: Aie Materials For Nlomentioning
confidence: 99%